Linear elastic properties of silicone rubbers filled with nano- and micro-silica particles - Tadaharu ADACHI (The Japan Society of Mechanical Engineers, 2020)
Linear elastic properties of the rubber composites filled with nano- and micro-particles were discussed on the basis of the experimental results for the silicone rubbers filled with the silica particles and theoretical analysis. Because the nano-particles behaved in the composite as apparent particles composed of the nano-particles and interphase layers formed on the particles, it was validated that Lewis and Nielsen’s mixture law with the apparent volume fraction could evaluated Young’s modulus of the rubber composite in linear elastic region of the measured tensile stress-strain relations. The proportional limit strain of the composite was formulated theoretically using the model in which the particles were distributed three-dimensionally and randomly. The analyzed limit strain was clarified to be valid by comparing with the measured results of the composites filled with the nano- and micro-particles when the (apparent) volume fraction of the particles was less than the threshold of the particle percolation, 0.3. Finally, stress-strain relations in the linear elastic region were shown specifically by using the analytical Young’s moduli and proportional limit strains for the composites.